Attitude of Business Students towards E-Commerce: A Case Study - Nawaz Ahmad; Syeda Tayyaba Fasih (International Journal of Experiential Learning & Case Studies, 2017)
This case study assesses the attitude of business students towards e-commerce subject offered in business schools comparing it with different other business subjects such as marketing, human resource, f inance, and supply chain etc. It discusses the emerging trends of e-commerce globally and its impact on Pakistan exploring the trends of e-commerce in Pakistan as well as the role of business schools in capitalising the industry of e-commerce by introducing e-commerce as a subject in their curriculum. The present case study identif ied the inclination of business students towards business studies and their ignorance of the emerging f ield of e-commerce as a subject study. It utilised survey questionnaire technique to gather data from 100 MBA students from f ive different business schools having basic knowledge about e-commerce. The f indings of the study, tabulated through the graphical presentation, highlighted the unawareness of the business students regarding the benefits of the emerging industry of e-commerce